CIVIC EDUCATION OF THE FUTURE SPECIALIST IN ECONOMICS (Pedagogy of Higher and Secondary Education, 2010)
The paper addresses the problem of civic education of the students of the enomic university, identified and justified especially the formation of citizenship.
Keywords: citizen; citizenship; civic education